Incidence and risk factors for retinopathy of prematurity in a Brazilian reference service - Gonçalves, Eduardo; Násser, Luciano Sólia; Martelli, Daniella Reis; Alkmim, Isadora Ramos; Mourão, Thalita Veloso; Caldeira, Antônio Prates; Martelli-Júnior, Hercílio (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Retinopathy of prematurity (ROP) is a known cause of blindness in which diagnosis and timely treatment can prevent serious harm to the child. This study aimed to evaluate the incidence of ROP and its association with known risk factors. DESIGN AND SETTING: Longitudinal incidence study in the neonatal intensive care unit (NICU) of Universidade Estadual de Montes Claros. METHODS: Newborns admitted to the NICU with gestational age less than 32 weeks and/or birth weight less than 1,500 grams, were followed up over a two-year period. The assessment and diagnosis of ROP were defined in accordance with a national protocol. The chi-square test or Fisher’s exact test were used to determine associations between independent variables and ROP. Analysis on the independent effect of the variables on the results was performed using multiple logistic regression. RESULTS: The incidence of ROP was 44.5% (95% confidence interval, CI = 35.6-46.1) in the study population. The risk factors associated with the risk of developing the disease were: birth weight less than 1,000 grams (odds ratio, OR = 4.14; 95% CI = 1.34-12.77); gestational age less than 30 weeks (OR = 6.69; 95% CI = 2.10-21.31); use of blood derivatives (OR = 4.14; 95% CI = 2.99-8.99); and presence of sepsis (OR = 1.99; 95% CI = 1.45-2.40). CONCLUSIONS: The incidence of ROP was higher than that found in the literature. The main risk factors were related to extreme prematurity.